Effectiveness of antiretroviral therapy among HIV-infected prisoners: reincarceration and the lack of sustained benefit after release to the community. - Springer, Sandra A; Pesanti, Edward; Hodges, John; Macura, Thomas; Doros, Gheorghe; Altice, Frederick L (Clinical infectious diseases : an official publication of the Infectious Diseases Society of America, 2004)
Responses to highly active antiretroviral therapy (HAART) in correctional settings and their sustained benefit in prisoners after release are currently not known. To examine the human immunodeficiency virus type 1 (HIV-1) RNA level (VL) and CD4 lymphocyte response to HAART during incarceration and upon reentry to the correctional system, we conducted a retrospective cohort study of longitudinally linked demographic, pharmacy, and laboratory data from the Connecticut prison system. During incarceration, the mean CD4 lymphocyte count increased by 74 lymphocytes/ mu L, and the mean VL decreased by 0.93 log10 copies/mL (P<.0001). Fifty-nine percent of the subjects achieved a VL of <400 copies/mL at the end of each incarceration period. For the 27% of subjects who were reincarcerated, the mean CD4 lymphocyte count decreased by 80 lymphocytes/ mu L, and the mean VL increased by 1.14 log10 (P<.0001). Although HAART use resulted in impressive VL and CD4 lymphocyte outcomes during the period of incarceration, recidivism to prison was high and was associated with a poor outcome. More effective community-release programs are needed for incarcerated patients with HIV disease.
Keywords: Antiretroviral Therapy, Highly Active; CD4 Lymphocyte Count; Cohort Studies; HIV Infections; HIV-1; Humans; Prisoners; Prisons; Retrospective Studies; Viral Load